DEPENDENCE RATIO ANALYSIS OF CITIES IN SOUTH SUMATRA RESULTS OF BPS SURVEY AND CENSUS FOR 2005-2020 - Suasti, Yurni; Putri, Hellen Apriani; Iskarni, Paus; Iswara, Dedi; Shinta, Ridvia (Sumatra Journal of Disaster, Geography and Geography Education, 2022)
This study aims to analyze the dependency ratio (Dependency Ratio) of cities in the province of South Sumatra in 2005 -2020. The analysis was carried out using secondary data from BPS surveys and censuses based on data from cities in South Sumatra Province and based on times series every five years in the last two decades. The research method used is a qualitative descriptive analysis method based on library research. The research subjects in this study were the population, both young people (0-14 years), productive age people (15-64 years) and old people (65+ years or more). As for the results obtained from the analysis, it can be concluded that the cities in South Sumatra Province, the age structure of the population is in the transition stage from a young population to an old population. The dependency ratio of cities in South Sumatra Province has continuously decreased since 2005-2020 until now it has entered the category of low dependency ratio. Keywords: Dependency Ratio, Productive Age, Non-productive Age,Cities